Procalcitonin, white blood cell count and C-reactive protein as predictors of S. aureus infection and mortality in infective endocarditis. (15th February 2020) - Tascini, Carlo; Aimo, Alberto; Arzilli, Chiara; Sbrana, Francesco; Ripoli, Andrea; Ghiadoni, Lorenzo; Bertone, Chiara; Passino, Claudio; Attanasio, Vittorio; Sozio, Emanuela; Taddei, Eleonora; Murri, Rita; et al.
Abstract: Background: Infective endocarditis (IE) is characterized by high rates of in-hospital death, and Staphylococcus aureus infection predicts a worse prognosis. We aimed to assess if admission inflammatory biomarkers (white blood cell – WBC – count, C-reactive protein — CRP, and procalcitonin) are informative on microbiological etiology and short-term outcomes. Methods: Data from 236 patients admitted for IE from January 2013 to June 2018 were retrieved from a multicenter registry. Results: Fifty-two patients (22%) were infected by S. aureus . WBC, CRP and procalcitonin had area under the curve (AUC) values for S. aureus infection of 0.595, 0.675, and 0.727, respectively. Adding procalcitonin to WBC improved discrimination over WBC alone ( p  = 0.045), and procalcitonin predicted S. aureus infection independently from the other inflammatory biomarkers and patient characteristics. Patients with WBC ≥ 12, 800/mm 3, CRP ≥ 130 mg/L, and procalcitonin ≥ 1.7 ng/mL had an almost 20-fold higher risk of S. aureus infection than patients with all biomarkers < cut-offs. AUC values for in-hospital death were 0.702, 0.725 and 0.727 for the WBC, CRP, and procalcitonin, respectively. Among inflammatory biomarkers, WBC and procalcitonin independently predicted in-hospital death. Procalcitonin refined risk stratification when added to WBC, and to the combination of WBC and CRP. Patients with WBC ≥ 10, 535/mm 3, CRP ≥ 85 mg/dL, and procalcitonin ≥ 0.4 ng/mL had a 27-fold higher risk of in-hospital death than patients with all biomarkers < cut-offs. Conclusions: Among patients with IE, high levels of inflammatory biomarkers on admission, particularly procalcitonin, are associated with a higher likelihood of S. aureus infection, and a higher risk of in-hospital mortality. Highlights: Infective endocarditis (IE) is characterized by high rates of in-hospital death. S. aureus infection predicts a worse prognosis. High levels of inflammatory biomarkers on admission predict S. aureus infection and in-hospital death. Procalcitonin is a particularly strong predictor.